1999
DOI: 10.1111/j.1469-8749.1999.tb00592.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual–proprioceptive mapping in children with developmental coordination disorder

Abstract: Developmental coordination disorder (DCD) occurs in a small but significant proportion of children who present with impaired body–eye coordination and show poor acquisition of motor skills. This study investigated the visual–proprioceptive mapping ability of children with DCD from a small selected group, with particular reference to the use of vision in matching tasks. The children with DCD in this study were significantly poorer than control children on all matching tasks. They seemed to have particular diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Fine motor skills are defined as smaller actions, such as grasping an object between the thumb and a finger or using the lips and tongue to feed (Mon-Williams et al, 1999). In our model, the horizontal rung walking task and the skilled reaching task both require fine motor coordination and learning.…”
Section: Motor Learning In Bxd Lines Of Micementioning
confidence: 99%
“…Fine motor skills are defined as smaller actions, such as grasping an object between the thumb and a finger or using the lips and tongue to feed (Mon-Williams et al, 1999). In our model, the horizontal rung walking task and the skilled reaching task both require fine motor coordination and learning.…”
Section: Motor Learning In Bxd Lines Of Micementioning
confidence: 99%
“…Children with poor somatosensory processing are often not diagnosed until they are around school age, when they present with significant motor deficits and are referred to pediatric occupational or physical therapists. Children with somatosensory deficits, observed when they are older, have difficulty functioning in their everyday lives (Blanche, Reinoso, et al., 2012 ; Falk et al., 2010 ; Fatoye et al., 2009 ; Johnston et al., 1987 ; Mon‐Williams et al., 1999 ; Schneck, 1991 ; Weimer et al., 2001 ), such as with feeding, dressing, and playing. Studies have linked poor proprioception with motor difficulties in older children, including poor balance and postural control (Blanche, Bodison, et al., 2012 ; Weimer et al., 2001 ), difficulties with force gradation (Dunn, 1999 ; Parham & Ecker, 2007 ), handwriting difficulties (Falk et al., 2010 ; Schneck, 1991 ), and poor coordination (Fatoye et al., 2009 ; Johnston et al., 1987 ; Mon‐Williams et al., 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…Children with somatosensory deficits, observed when they are older, have difficulty functioning in their everyday lives (Blanche, Reinoso, et al., 2012 ; Falk et al., 2010 ; Fatoye et al., 2009 ; Johnston et al., 1987 ; Mon‐Williams et al., 1999 ; Schneck, 1991 ; Weimer et al., 2001 ), such as with feeding, dressing, and playing. Studies have linked poor proprioception with motor difficulties in older children, including poor balance and postural control (Blanche, Bodison, et al., 2012 ; Weimer et al., 2001 ), difficulties with force gradation (Dunn, 1999 ; Parham & Ecker, 2007 ), handwriting difficulties (Falk et al., 2010 ; Schneck, 1991 ), and poor coordination (Fatoye et al., 2009 ; Johnston et al., 1987 ; Mon‐Williams et al., 1999 ). Although studies have shown, in adults and animal models, loss of proprioception can be accommodated by increasing reliance on visual feedback (Bard et al., 1995 ; Bernier et al., 2006 ; Bossom & Ommaya, 1968 ; Ingram et al., 2000 ; Miall et al., 2018 ), this process is highly cognitive intensive (Ingram et al., 2000 ; Miall et al., 2018 ) and thus results in less efficient movement patterns (Sainburg et al., 1995 ).…”
Section: Introductionmentioning
confidence: 99%
“…It may be argued, however, many of these supposed tests of kinaesthesis are flawed: for instance, many tests require a relational judgement ('which hand is higher'); impose a memory load (e.g. movement reproduction); or test the egocentric mapping of kinaesthetic cues rather than kinaesthetic sensitivity per se (see Wann 1991, Smyth and Mason 1998, Mon-Williams et al 1999). Controversy also exists over the level of 'kinaesthetic sensitivity' in young children (cf.…”
mentioning
confidence: 99%